Culture Shock and Academic Adaptation: The Experiences of Patani Students in Islamic Higher Education - Muhammad Nurfazri; Hapid Ali; Ai Rida Himatulaliah (KEDJATI Journal of Islamic Civilization, 2024)
Cultural differences between countries often lead to culture shock, particularly among students pursuing higher education abroad. It is also encountered by Patani students studying at UIN Sunan Gunung Djati Bandung, which affects their academic experience. Thus, this study explores the culture shock experienced by Patani students, focusing on their academic adaptation process on campus. A qualitative approach was employed by interviewing Patani students from several departments to gain insights into their adaptation challenges and needs. The findings reveal that Patani students face several obstacles, including language barriers, limited social support, and challenges adjusting to differences between Sundanese and Patani cultures. Many students expressed the need for language classes and specialized support services for international students to ease their academic and social transition. Besides, these findings highlight the importance of universities providing adequate support systems for international students. Institutions should consider implementing language programs and dedicated services to help non-local students integrate more effectively into academic and social settings. Addressing the adaptation challenges of international students, particularly those in non-international class settings, can enhance their academic success and overall campus experience. This study underscores the need for universities to be more attentive to the specific needs of international students to foster a more inclusive academic environment.